Cognitive Function Impairment in Patients with Neuropathic Pain Under Standard Conditions of Care - Povedano, Mónica; Gascón, Jordi; Gálvez, Rafael; Ruiz, Manuel; Rejas, Javier (Journal of pain and symptom management, 2007)
The objective of this study is to analyze the prevalence to cognitive function impairment (CI) in a pragmatic cohort of subjects with different types of neuropathic pain under standard conditions of care by means of a cross-sectional baseline analysis of a sample of patients with NeP enrolled in a pragmatic, prospective, multicenter study evaluating the effectiveness of gabapentin. A total of 1519 patients (58.8% women), aged ≥18 years (mean [SD] = 56.0 [13.7]), with neuropathic or mixed neuropathic and nociceptive pain for a mean (SD) of 1.1 (2.8) years were enrolled in the study. Pain was assessed with the short form of the McGill Pain Questionnaire, and cognitive function was measured with the Mini-Mental State Examination (MMSE). A score ≤24 on the MMSE was considered as CI. Multivariate logistic regression models were used to estimate CI prevalence. CI prevalence was substantially higher in patients with NeP than that reported in the general Spanish population, and significantly higher than in patients with mixed neuropathic and nociceptive pain: 11.4% (8.5%–14.3%) vs. 6.4% (4.6%–8.7%), P = 0.006 (adjusted odds ratio = 1.88 [1.21–2.91]). Prevalence significantly increased with age, up to 32.2% (20.6%–45.6%) in those with NeP, and to 28.2% (15.0%–44.9%) in those with mixed syndromes, for the age group ≥75 years, P < 0.001 within age groups. Symptoms of anxiety and obesity, and to a lesser extent, symptoms of depression, were also factors associated with a higher prevalence rate of CI. This analysis showed that, after adjusting for confounding factors, the prevalence of CI was substantially higher in patients with NeP than those with mixed pain and the reference general population. Age, anxiety, depression, and obesity were factors found to be significantly associated with CI.